An Investigation into Language of Attitude in Remarks of English and Vietnamese Music Gameshows from the Frameworks of Appraisal. - Lê Phạm Uyên Trúc (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study aims to investigate the language of Attitude in remarks of English and Vietnamese MGs, looking at the semantic features of the language of Attitude as represented through English and Vietnamese MGs. This study is expected to provide better insights into the attitudinal aspects of evaluative language in English and Vietnamese so that implications could be made for language teaching and learning, for the field of translation, and SFL research.